Sectoral Effects of Monetary Policy: Evidence from Pakistan (The Pakistan Development Review, 2006)
Does monetary policy have economically significant effects on the real output? Historically, economists have tended to hold markedly different views with regard to this question. In recent times, however, there seems to be increasing consensus among monetary economists and policy-makers that monetary policy does have real effects, at least in the short run.1 Consequently, focus of monetary policy analysis has recently shifted from the big question of whether money matters, to emphasising other aspects of monetary policy and its relations to real economic activity. One aspect that has received considerable attention of late is the sectoral or regional effects of monetary policy shocks. Recent studies on the subject make it quite clear that different sectors or regions of the economy respond differently to monetary shocks. This observation has profound implications for the macroeconomic management as the central bank will have to weigh the varying consequences of its actions on different sectors or regions of the economy. For instance, the tightening of monetary policy might be considered mild from the aggregate perspective, yet it can be viewed as excessive for certain sectors. If this is true then monetary policy should have strong distributional effects within the economy. Accordingly, information on which sectors react first and are more adversely affected by monetary tightening provides valuable information to monetary authorities in designing appropriate monetary policies. Additionally, the results can contribute to our understanding of the underlying nature of transmission mechanism. And for that reason, many economists have called for a disaggregated analysis of monetary transmission mechanism [e.g., Domac (1999), Dedola and Lippi (2005), Ganley and Salmon (1997), Carlino and DeFina (1998)].